2020
DOI: 10.22452/mjes.vol57no1.6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Innovation on Economic Growth: Evidence from Malaysia

Abstract: This study empirically investigates the effect of innovation on economic growth using the neoclassical economic growth model. Embarking from the traditional labour growth, physical capital and human capital framework, innovation is postulated to be the main driver for robust economic growth. Using time series techniques, we discover very attention-grabbing findings that highlight the impact of innovation on economic growth for Malaysia. First, the innovation measured by the quantity of a total number of a pate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 34 publications
1
22
0
2
Order By: Relevance
“…It is also in line with (Mohamed et al 2021 ) since their estimation of the rate of growth of the Egyptian economy per capita gross domestic product has a complementary relationship with the rate of growth of the Egyptian economy's technological innovation. According to Law et al ( 2020 ), insufficient innovation technology flows over the long term negatively affect Malaysia's innovation capacity. A study by Fan et al ( 2018 ) found that technological innovation in the short run can positively and significantly influence the industrial growth of Bangladesh, but that it has a negative impact in the long run.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…It is also in line with (Mohamed et al 2021 ) since their estimation of the rate of growth of the Egyptian economy per capita gross domestic product has a complementary relationship with the rate of growth of the Egyptian economy's technological innovation. According to Law et al ( 2020 ), insufficient innovation technology flows over the long term negatively affect Malaysia's innovation capacity. A study by Fan et al ( 2018 ) found that technological innovation in the short run can positively and significantly influence the industrial growth of Bangladesh, but that it has a negative impact in the long run.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…The discussion on economic growth and its proposed determinants has been a continuous and significant academic endeavor (Law et al, 2020). This paper has attempted to summarize Brazil's economic growth from a very long-run perspective (1822-2019), in a structured qualitative and narrative review that encompasses three main contributions, at the theoretical, empirical, and policy levels.…”
Section: Discussionmentioning
confidence: 99%
“…La innovación es un proceso natural para el desarrollo humano y es un elemento esencial para el desarrollo de las economías (Zilibotti, 2008;Law et al, 2020) porque la innovación propicia competitividad y esta, a su vez, expansión de los mercados, que por ende trae crecimiento de la economía y mayor bienestar social (Galindo Martín et al, 2012).…”
Section: La Innovación Industrialunclassified